المسؤولية الاجتماعية ودور الفرد في سعادة المجتمع في السيرة النبوية: Responsibilities of Person for Welfare of Society in the Light of Sirat Al-Nabi (ﷺ) - Dr. Muhammad Abdul Razzaq Aswad (Seerat Studies, 2023)
The Messenger of Allah, ╓azrat Mu╒ammad (SAW) has presented his life and character as an example for man and society. A Muslim should play his due role at every stage for reformation and benevolence of society. The respected Holy Prophet (SAW) declared it a great virtue to be affectionate, co-operative and resourceful for each other. He proclaimed that no Muslim can be a perfect Muslim unless he desires same for the other Muslim which he desires for himself. The best of the Muslims is one who is more useful and kinder for society and his fellow beings. The term “Social Responsibilities” is not visible and found in the books of old authentic great writers. It is a modern term and it means that every member of society must feel his responsibility. He must play his role for positive changes in society and take part in all virtuous deeds and activities. He may not be involved in violation of law and order. The Holy Prophet (SAW) has made every member of society responsible for leading the life of purpose and mission. This research article thoroughly throws light upon this theme.